Defence Dilemmas of the GCC States – Threats and Military Build-Up - Czulda, Robert (International Studies. Interdisciplinary Political and Cultural Journal, 2018)
Although regional states don`t seek war, it cannot be ruled out that an unfavourable development in the international arena could lead to an unintended outbreak of a full-scale conflict, which would either directly or indirectly involve the Arab monarchies. In response to several threats within their proximity, these states have, for years, been pursuing several initiatives aimed at increasing their deterrence potential and interoperability in case of a crisis. The main goal of this article is to present and assess the GCC’s threat perception, followed by an analysis of the multilateral and unilateral responses. The main research question concerns the degree to which the GCC states are able to establish a joint and effective military bloc within the Persian Gulf.